(untitled) (American Journal of Applied Statistics and Economics, 2025)
This study investigates within Covariance-based Structural Equation Modeling (CV-SEM) the potential causal relationships between Islamic equity-based financing and Nigerian Small Scale Enterprises (SSEs) expansion. A quantitative survey design was employed to collect questionnaire-based, cross-sectional primary data from 512 educated SSE owners and managers in eight business districts in the Abeokuta metropolis. STATA 12.1 software was utilized to estimate CV-SEM with the maximum likelihood method. Intuitively, the Principal Component Analysis (PCA) estimator was applied to derive continuous data scores for the latent variables. The fit indices tested (RMSEA, CFI and TLI) indicate that the study structural models fit the observed data. From the CV-SEM estimations, musharakah and mudharabah have potentially positive and significant impacts on the sales growth of SSEs in the study area. Findings reveal further that Islamic equity financing tools such as musharakah, diminishing musharakah, and mudharabah are more likely to enhance the development of SSEs in the Abeokuta metropolis significantly and indirectly through the Islamic finance legal framework. The study affirms that the expansion of small enterprises in the study area will be directly, positively, and significantly influenced by Islamic shared finance (Musharakah) and Islamic joint partnership (Mudharabah). However, the indirect positive and significant impact of Islamic equity finance through a legal framework (mediating factor) is stronger for the development of small firms than the direct impact. The study advocates that the federal government of Nigeria should institute a suitable legal framework for Islamic equity financing to enhance the operational capacity of small-scale businesses.